2021
DOI: 10.1021/acschembio.1c00324
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 Programmed −1 Ribosomal Frameshifting Element Crystal Structure Solved to 2.09 Å Using Chaperone-Assisted RNA Crystallography

Abstract: The programmed −1 ribosomal frameshifting element (PFSE) of SARS-CoV-2 is a well conserved structured RNA found in all coronaviruses’ genomes. By adopting a pseudoknot structure in the presence of the ribosome, the PFSE promotes a ribosomal frameshifting event near the stop codon of the first open reading frame Orf1a during translation of the polyprotein pp1a. Frameshifting results in continuation of pp1a via a new open reading frame, Orf1b, that produces the longer pp1ab polyprotein. Polyproteins pp1a and pp1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(112 citation statements)
references
References 65 publications
(302 reference statements)
11
74
1
Order By: Relevance
“…It was demonstrated that the PFS element sequence alone could recapitulate the PFS activity without a protein cofactor in SARS-CoV ( Baranov et al, 2005 ). The pseudoknotted structure was observed in NMR ( Liphardt et al, 1999 ), chemical probing ( Huston et al, 2021 ), cryo-EM (complexed with an elongating ribosome) ( Bhatt et al, 2021 ), and X-ray crystallography ( Roman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the PFS element sequence alone could recapitulate the PFS activity without a protein cofactor in SARS-CoV ( Baranov et al, 2005 ). The pseudoknotted structure was observed in NMR ( Liphardt et al, 1999 ), chemical probing ( Huston et al, 2021 ), cryo-EM (complexed with an elongating ribosome) ( Bhatt et al, 2021 ), and X-ray crystallography ( Roman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The high flexibility and plasticity of the FSE is an essential requirement for its biological activity (23,(46)(47)(48)(49). This unique characteristic is also supported by cryo-EM and x-ray structures recently published (34,44,51). In particular, the pseudoknot structure seems to be highly dynamic before encountering the ribosome.…”
Section: Discussionmentioning
confidence: 81%
“…The presence of a central ring is shown in yellow. (D) Crystallographic structures of the free PFSE (PDB:7mlx) [ 26 ] (left) and (PDB:7mky) [ 27 ] (right). The stems S1 (green), S2 (blue) and S3 (orange) are shown.…”
Section: Translation Of Viral Transcriptsmentioning
confidence: 99%
“…Then, X‐ray crystallography studies showed that the structure of the pseudoknot is formed by three H‐type stems stacked in a vertical orientation (Fig. 1D ): These structures bring interaction details at atomic resolution that will be useful for the identification of binding sites of specific ligands and for the drug design of antiviral compounds that will target specifically the PFSE [ 26 , 27 ]. In addition, a short isoform of the host zinc‐finger antiviral protein ZAP‐S directly interacts with the PFSE and thereby modifies its folding, leading to downregulation of −1 frameshifting [ 28 ].…”
Section: Translation Of Viral Transcriptsmentioning
confidence: 99%